Checklist of raphignathoid mites (Acari: Raphignathoidea) of Turkey - Doñan, Sal§H (Zootaxa, 2007)
The list contains 112 raphignathoid mite species (Acari: Raphignathoidea) in 6 families known from Turkey. It is expected that the number of raphignathoid species in Turkey which inhabit different biotopes and climatic conditions will grow as comprehensive surveys continue. The most diverse family, Stigmaeidae, is represented by 51 species (46%) and the second one, Camerobiidae, is represented by 24 species (21%).